Changing physician behavior: interventions to improve prescription writing practices in a secondary level hospital in Delhi - Routray, Dipanweeta; Sahoo, Jyotiranjan; Singh, Prateek; Das, Kulen; Singh, Satyavir (International Journal of Basic & Clinical Pharmacology, 2017)
Background: According to a report by World Health Organization (WHO) in 2003, approximately 50% of all patients fail to take their medicine correctly. This is due to errors in prescription, underuse or misuse of medicines and ignorance of prescribers, dispensers, and patients. Methods: It is a hospital-based interventional-study carried out in a secondary level multispecialty hospital of Delhi. Investigators collected 536 prescriptions from the outpatient department of various departments and studied according to WHO core prescribing indicators for assessing drug prescription writing pattern. Interventions to improve the prescribing pattern included one continued medical education session and one workshop on prescription writing (providing essential drug list [EDL] etc.,), sharing the baseline data with the physicians and administrative approach. Evaluation of the prescribing pattern after 6 weeks of the intervention was done to find out the impact. Results: On an average 3.43 drug per encounter before intervention increased to 3.46 drugs per encounter. Inclusion of generic drugs and from EDL increased significantly from 54.8% to 73.4% and 76.9% to 88.4% respectively.. Prescribing antibiotics and injectables showed no significant reduction from baseline. The completeness of the prescriptions with respect to the various components improved significantly. Conclusion: Combining different intervention seems a noble approach to improve the prescription writing practices with respect to completeness and inclusion of generic drugs, drugs from EDL.